Analysis of Productivity Elements of Winter Barley Varieties in the Conditions of the Central Region of Uzbekistan - Khudaykulov, J. B.; Shavkatova, Z. Sh. (American Journal of Botany and Bioengineering, 2025)
Relevance and necessity of the topic. Description. Barley is a cereal, a member of the grass family with edible grains. Its flowers are clusters of spikelets arranged in a distinctive herringbone pattern. Each spikelet has a long thin awn (to 160 mm (6.3 in) long), making the ears look tufted. The spikes are in clusters of three. In six-row barley, all three spikes in each cluster are fertile; in two-row barley, only the central one is fertile [2]. It is a self-pollinating, diploid species with 14 chromosomes [3].